The view from Saturday [compact disc, unabridged] - Konigsburg, E. L. (Listening Library, 2004)
Four students, with their own individual stories, develop a special bond and attract the attention of their teacher, a paraplegic, who chooses them to represent their sixth-grade class in the Academic Bowl competition.